Patient-reported outcome (PRO) as an addition to long-term results after high-precision stereotactic radiotherapy in patients with secreting and non-secreting pituitary adenomas: A retrospective cohort study up to 17-years follow-up - Kessel, Kerstin A.; Diehl, Christian D.; Oechsner, Markus; Meyer, Bernhard; Gempt, Jens; Zimmer, Claus; Schmidt-Graf, Friederike; Combs, Stephanie E. (Cancers, 2019)
High-precision radiotherapy has been established as a valid and effective treatment option in patients with pituitary adenomas. We report on outcome after fractionated stereotactic radiotherapy (FSRT) in correlation with patient-reported outcomes (PROs). We analyzed 69 patients treated between 2000 and 2019. FSRT was delivered with a median total dose of 54 Gy (single fraction: 1.8 Gy). PRO questionnaires were sent to 28 patients. Median overall survival was 17.2 years; mean local control was 15.6 years (median not reached). Median follow-up was 5.8 years. Twenty (71%) patients participated in the PRO assessment. Physicians reported symptoms grade ≥3 in 6 cases (9%). Of all, 35 (51%) patients suffered from hypopituitarism at baseline, and during follow-up, new or progressive hypopituitarism was observed in 11 cases (16%). Patients reported 10 cases of severe side effects. Most of these symptoms were already graded as CTCAE (Common Terminology Criteria for Adverse Events) grade 2 by a physician in a previous follow-up exam. PROs are an essential measure and only correlate to a certain extent with the physician-reported outcomes. For high-precision radiotherapy of pituitary adenomas, they confirm excellent overall outcomes and low toxicity. In the future, the integration of PROs paired with high-end treatment will further improve outcomes.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Long-term survival; Patient-reported outcome; Pituitary adenoma; Secreting; Stereotactic fractionated radiotherapy; Toxicity